2019
DOI: 10.1080/13621718.2018.1556436
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of strain and strain rate during rapid cooling friction stir welding of pure copper

Abstract: The strain and strain rate during friction stir welding was evaluated by measuring the distortion of the marker material. A thin Cu-40Zn foil as marker was inserted into the butting surface of two pure copper workpieces and the tool 'stop action' was employed. The results show that the strain in the shoulder-affected zone increases in a two stair-step shape as the material flows from the front to the rear of the tool, corresponding to the first accelerated and then decelerated flow stages. However, the strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 25 publications
2
36
0
Order By: Relevance
“…The deformation status of pure Mg material at different positions can be obtained according to the shape and size of the marker. Compared with the study of Liu et al (2019b), there exists obvious difference in the flow behavior of metals, resulting in different deformation states of the markers on the upper and lower surfaces. The appearance of this phenomenon is related to the nature of the material itself, which is affected by the shape of the stirring probe and the processing parameters (Han et al, 2019).…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…The deformation status of pure Mg material at different positions can be obtained according to the shape and size of the marker. Compared with the study of Liu et al (2019b), there exists obvious difference in the flow behavior of metals, resulting in different deformation states of the markers on the upper and lower surfaces. The appearance of this phenomenon is related to the nature of the material itself, which is affected by the shape of the stirring probe and the processing parameters (Han et al, 2019).…”
Section: Methodsmentioning
confidence: 95%
“…Nevertheless, the strain could not be obtained directly but reversely derived from the strain rate. Liu et al (2019a;2019b) developed an experimental method by inserting the marker to approximately determine the strain and strain rate during FSW process of pure copper. However, the detailed microstructural evolution was not involved in this study.…”
Section: Introductionmentioning
confidence: 99%
“…It is environmentally friendly (a green process) because there are no toxic fumes and radiation. Therefore, FSW has been widely used in joining highstrength aluminum alloys and other difficult welding metals in aerospace, shipbuilding, automobile and railway industries [2][3][4]. Due to the remarkable success of FSW, the friction stir concept has been further modified, improved and refurbished to develop various novel material joining and processing technologies for other sophisticated applications [5].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, FSW of copper and it alloys (specially the CuZn or brass alloys) has been investigated by researchers [6][7][8][9][10][11][12][13][14][15][16]. For example, Heidarzadeh et al [6] have compared the FSW of single and double phase brass alloys.…”
Section: Introductionmentioning
confidence: 99%
“…They have shown discontinuous dynamic recrystallization (DDRX) in conjunction with annealing twinning is the grain structure formation during FSW. Liu et al [12] have evaluated the strain and strain rate during rapid cooling friction stir welding of pure copper. Their results showed that the strain in the shoulder-affected zone increases in a two stair-step shape as the material flows from the front to the rear of the tool, corresponding to the first accelerated and then decelerated flow stages.…”
Section: Introductionmentioning
confidence: 99%